The Choice Of The Operation Method For Combined Ulcer Of Gaster And Duodenum - A.A. Tursumetov, T.A. Askarov, H.M. Jafarov, Z.Z. Tukhtamurod (International Journal of Advanced Science and Technology, 2020)
The 30-year experience of surgical treatment of 354 patients with combined gastric and duodenal ulcers is presented (type II ulcers according to Johnson H.D., 1965). Every third patient (32.8%) had ulcers “difficult” for resection of the stomach, gigantic in size, high in localization, multiple in number and their combinations. Recent features of the typology of ulcers dictated the choice of method and volume of gastric resection, performed, as a rule, in an atypical version.